Teacher Candidates' Perceptions of Emergent Teacher Leadership in Clinically Based Teacher Education. (2nd October 2022) - Rutten, Logan; Doyle, Sebrina L.; Wolkenhauer, Rachel; Schussler, Deborah L.
ABSTRACT: Emergent teacher leadership is a new concept that refers to teacher leadership in its earliest forms among teachers at any point in their careers but particularly among teacher candidates and early-career teachers. This qualitative study used semi-structured interviews to investigate how six teacher candidates perceived their own emergent teacher leadership as they completed yearlong clinical internships in a professional development school (PDS) in which teacher educators had established teacher leadership development as a formalized expectation for all teacher candidates. Thematic analysis of the interview transcripts revealed that although the teacher candidates maintained aspirations for future teacher leadership, they struggled throughout their internships with feelings of illegitimacy as teacher leaders and with skepticism toward the PDS's expectations for teacher leadership – even as they gradually began to describe their engagement in leadership practices throughout the PDS. Teacher candidates reported leading when they were included within PDS decision-making processes and when they created their own leadership opportunities by taking the initiative and by gathering others to share ideas and to learn together through practitioner inquiry. The findings suggest that teacher educators could promote emergent teacher leadership by assisting teacher candidates in connecting the practices of practitioner inquiry with leadership opportunities and practices.